Conversion to generic cyclosporine A in stable chronic patients after heart transplantation - Kräuter, Maximilian; Helmschrott, Matthias; Erbel, Christian; Gleißner, Christian A.; Frankenstein, Lutz; Schmack, Bastian; Ruhparwar, Arjang; Ehlermann, Philipp; Katus, Hugo; Dösch, Andreas (Drug design, development and therapy, 2013)
Conversion to generic cyclosporine A in stable chronic patients after heart transplantation Maximilian Kraeuter,1 Matthias Helmschrott,1 Christian Erbel,1 Christian A Gleissner,1 Lutz Frankenstein,1 Bastian Schmack,2 Arjang Ruhparwar,2 Philipp Ehlermann,1 Hugo A Katus,1 Andreas O Doesch1 1Department of Cardiology, 2Department of Cardiac Surgery, University of Heidelberg, Heidelberg, Germany Background: Cyclosporine A (CSA) is a narrow therapeutic index drug. Available CSA products differ in the constitution of their emulsion. To compare intra-individual differences after a conversion to a generic CSA, a retrospective single-center study was initiated. Methods: Twenty adult stable chronic (>24 months post heart transplant) recipients were included in the present retrospective study. These patients were previously switched from Sandimmune Neoral® to the generic CSA (Equoral®) according to the patients’ preference during the clinical routine. Dose-normalized trough levels (DNL) and trough levels (C0) at 8 months, 4 months, and 2 weeks before the switch were retrospectively compared with the corresponding values at 2 weeks, 4 months, and 8 months after the switch to the generic CSA. Additionally, changes in the routine laboratory parameters, the number of treated rejection episodes, and the adherence to the CSA target levels were compared. Results: The mean DNL (adapted to the daily CSA dose in mg) was 0.71±0.26 (ng/mL)/mg on Neoral therapy; on Equoral it was 0.68±0.23 (ng/mL)/mg, (P=0.38). In comparison to the CSA daily dose prior to the conversion, at postconversion, no significant changes of CSA daily dose were observed (Neoral 140.67±39.81 mg versus Equoral 134.58±41.61 mg; P=0.13). No rejection episodes requiring therapy occurred prior to or postconversion (P=0.99). Additionally, no statistically significant changes of routine laboratory parameters regarding the Modification of Diet in Renal Disease or hematological parameters were seen (all P=not significant). No adverse events after the conversion were observed. Conclusion: This study in chronic and stable HTx patients demonstrated no statistically significant differences in the CSA DNL after a conversion to generic CSA (Equoral). The generic CSA was generally well-tolerated. We concluded that a conversion from Neoral to Equoral is safe and clinically feasible in this distinct patient population. However, multiple switches between different generic immunosuppressants must especially be avoided in the interest of patient safety, and close follow-up examinations must be warranted. Keywords: heart transplantation, immunosuppression, generic cyclosporine A